Education for democracy : a renewed approach to civic inquiries for social justice - Camicia, Steven Paul; Knowles, Ryan (Teaching and learning social studies., 2021)
This book presents a vision of education for democracy built around promoting equity and social justice. In doing so, Camicia and Knowles challenge many of the common perspectives of democratic education, deliberation, and the common good. The authors have published widely on the topic of education for democracy. This book builds upon their work to assist practicing teachers, teacher educators, graduate students, and educational researchers in understanding the background of education for democracy, as well as new directions for the field.While one of the primary goals of public schools is to teach students how to build better communities, this goal is increasingly difficult given the degree of political polarization within societies. Recent events provide no shortage of challenges to democracy in the United States and beyond. Utilizing theory and research, Camicia and Knowles promote instructional methods that are responsive to changing cultural and political contexts. There is an increasing need to rethink democratic principles and how these principles might be supported in classrooms in order to teach for social justice. This requires a move away from often stated idealistic notions of deliberative democracy, toward a perspective of education for democracy that incorporates aspects of identity, interests, and inequitable power relations within society.